DESIGN AND VALIDATION OF 5 KW HORIZONTAL AXIS THREE-BLADED SMALL WIND TURBINE - Andika Satria, Abraham
In the past few decades, wind energy played an increasingly significant role acting as a reliable and sustainable energy source. It has become as competitive as nuclear or fossil sources. Furthermore, small wind turbines can help provide cheaper and cleaner energy in poor and rural areas, as demonstrated by many projects around the world. Thus, it is essential for engineers to help develop SWT for use in regions with low electrification coefficient. This research aims to design a horizontal-axis three-bladed Small Wind Turbine with a design power of 5 kW, as well as validating the wind turbine with a MATLAB-implemented Blade Element Momentum (BEM) method algorithm. The design process starts with selecting and calculating initial design parameters such as power and operating wind speeds. The next step is airfoil selection according to criteria that fulfills Small Wind Turbine requirements. Then, the calculation of optimum blade dimensions and modelling using QBlade. The simulation is carried out using the QBlade BEM simulation modules, which also provide control settings that results in an ideal power curve. A MATLAB code is created by implementing the BEM method and then used to validate the wind turbine design. At design wind speed of 9.5 m/s, the QBlade simulation shows that the wind turbine has a potential to generate up to 5900 Watts when it operates at its optimum power coefficient. The corresponding tip speed ratio also indicates that it is operating at a safe speed, as it is slightly lower than the design value. The desired control setting is a variable speed-variable pitch (VS-VP) strategy, which is successful in achieving the ideal power curve. The wind turbine operation using the VS-VP strategy is validated with an average error margin of 7.2%.